The Post-Crisis Phillips Curve: A New Empirical Relationship between Wage and Inflation - Liviu Voinea (Global Labor Organization (GLO), 2019)
In this paper we test a new empirical relationship between wage and inflation. We introduce the concept of a cumulative wage gap, meaning the cumulative gap between the current wage and a maximum peak wage value in the past. In a crisis, people relate to their peak gains in the immediate past. We assume that people judge their consumption decisions based on the relation between their current wages and their past wages, adjusted for inflation. We call this the post-crisis Phillips Curve. The shape of the post-crisis Phillips Curve expresses the theoretical assumption that the inflation rate stays below its target until the cumulative real wage gap closes, and that it increases above its target when the cumulative real wage gap becomes positive. We test our hypothesis using data for 35 OECD countries for the period 1990-2017. We are able to confirm our hypothesis, as the coefficients have the expected sign and are statistically significant for the OECD panel as well as for most of the individual countries. We also find a break in the slope of the curve, as the coefficients are higher after the cumulative wage gap closes.
Keywords: E21; E24; E31; 330; wage; cumulative wage gap; inflation; Phillips Curve; monetary policy